Analysis of Building Integrated Photovoltaic Application for Apartment Building in Jakarta - Sandhika Adlisia Puspa Harani; Sunarto Sunarto (Jurnal Inovasi Konstruksi, 2022)
In sustainable development concept, energy efficiency and conservation measurements are paramount to reduce the level of building energy consumption. Utilization of such device diminishes the building dependency to the grid which is still dominated by energy from fossil fuels. Implementation of BIPV (Building Integrated Photovoltaic) system is expected to be one of the best possible choices for a tropical country such as Indonesia with abundance of solar radiation. With the existence of BIPV system, it is also expected to reduce the burden of electricity cost for the building management and occupants. This research is considerably new for government building and it also generates a formula to calculate minimum area and the amount of PV panels needed for apartment in Jakarta. Pasar Jumat Apartment is selected to be a subject for this research as the apartment is classified government building which was built and managed by Ministry of Public Work and Housing. Moreover, the apartment has modelled with BIM and already had green building concept.  It is expected that BIPV system can enhance the building performance through energy efficiency. However, more in-depth research work to the efficiency and economic feasibility of BIPV system installation are required before implementing the system on the building. Several options of PV panel installation are measured to figure out the most optimal PP (Payback Period) and BCR (Benefit Cost Ratio). Based on the physical feasibility and financial analysis, BIPV system is found to be more promising and profitable if it is implemented at "Pasar Jumat Apartment" for a long term in the future.